2009
DOI: 10.1073/pnas.0906753106
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the abundant nuclear factor poly(ADP-ribose) polymerase-1 by Helicobacter pylori

Abstract: Modification of eukaryotic proteins is a powerful strategy used by pathogenic bacteria to modulate host cells during infection. Previously, we demonstrated that Helicobacter pylori modify an unidentified protein within mammalian cell lysates in a manner consistent with the action of a bacterial ADP-ribosylating toxin. Here, we identified the modified eukaryotic factor as the abundant nuclear factor poly(ADP-ribose) polymerase-1 (PARP-1), which is important in the pathologies of several disease states typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Chen et al (49) previously demonstrated that incubating BGC-823 gastric cancer cells with H. pylori extract induced a breakdown of caspase-1 and caspase-3, but not of PARP. Nossa et al (50) subsequently demonstrated that PARP-1 became activated in H. pylori infected gastric epithelial cells. Notably, the present study similarly demonstrated that PARP-1 expression levels were significantly increased in H. pylori infected gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (49) previously demonstrated that incubating BGC-823 gastric cancer cells with H. pylori extract induced a breakdown of caspase-1 and caspase-3, but not of PARP. Nossa et al (50) subsequently demonstrated that PARP-1 became activated in H. pylori infected gastric epithelial cells. Notably, the present study similarly demonstrated that PARP-1 expression levels were significantly increased in H. pylori infected gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori ) cancers remains to be evaluated clinically. Few studies have demonstrated suppression of the inflammatory response by PARP inhibitors in mice infected with H. pylori (Nossa et al , 2009) and prevention of the formation of Helicobacter -induced precancerous conditions in mice deficient of anti-inflammatory cytokine. PARP-1 sits at the center of the game not only to assist in repair of RONS-induced DNA lesions, but it also can contribute to further damage by promoting inflammation.…”
Section: Interplay Between Infection-induced Inflammation and Dna Repairmentioning
confidence: 99%
“…To accomplish this simplification, researchers have previously introduced macromolecules into cells by many different methods, including viral transduction 10 , microinjection 11 , scrape loading 12,13 , cell fusion with chemically induced microinjection 14 , proprietary protein “transfection” reagents 15 , calcium phosphate precipitations 16 , and electroporation 17-20 . The introduced molecules range from nucleic acids including DNA, RNA, & RNAi species to proteins, cell-impermeable dyes, and antibodies for intracellular targets 21,22 .…”
Section: Introductionmentioning
confidence: 99%